Alcohol Consumption among the Oldest Old and How It Changes during Two Years. (18th December 2013) - Fornazar, Robin; Spak, Fredrik; Dahlin-Ivanoff, Synneve; Wilhelmson, Katarina
Abstract : This longitudinal study aimed to examine the pattern of alcohol consumption (using the AUDIT-C) among the oldest old (80+) and how it changed two years later. Five hundred seventy-six persons from the Gothenburg metropolitan area were interviewed between 2008 and 2011. Men represented a higher proportion of at-risk consumers (21.8%) than women (14.5%), but there was no sex difference in binge drinking (13.8% versus 12%). Men decreased their weekly consumption and also the proportion of binge drinking, and women decreased only in binge drinking. Further studies of the causality between alcohol consumption and health are suggested.